Impact of Music Education on Mental Health of Higher Education Students: Moderating Role of Emotional Intelligence - Wang, Feng; Huang, Xiaoning; Zeb, Sadaf; Liu, Dan; Wang, Yue (Frontiers in Psychology, 2022)
Music education is one of human kind most universal forms of expression and communication, and it can be found in the daily lives of people of all ages and cultures all over the world. As university life is a time when students are exposed to a great deal of stress, it can have a negative impact on their mental health. Therefore, it is critical to intervene at this stage in their life so that they are prepared to deal with the pressures they will face in the future. The aim of this study was to see how music education affects university students' mental health, with emotional intelligence functioning as a moderator. The participants in this research were graduate students pursuing degrees in music education. Non probability convenience sampling technique was used to collect and evaluate the data from 265 students studying in different public and private Chinese universities. The data was gathered at a time, and therefore, the study is cross-sectional. The data was collected from January 2022 till the end of March 2022. Many universities have been closed because to COVID-19, therefore data was also gathered online through emails. The data was analyzed quantitatively using the partial least squares (PLS)–structural equation modelling (SEM) technique. The findings backed up the hypotheses. The results revealed that there is a significant effect of music education on student’s mental health. Also, emotional intelligence as a moderator significantly and positively moderates the relationship between music education and students' mental health. Music has numerous physiological aspects, and listening to it on a daily basis may be beneficial to your general health and well-being. Furthermore, musicians and music students with a high level of emotional intelligence have a better chance of not just performing well in school, college and university or in the music industry, but also of maintaining mental health and improving it.